New Mexico and the Pimería Alta: the colonial period in the American Southwest - Douglass, John G., editor; Graves, William M., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2017)
Focusing on two areas of the Southwest that witnessed intensive and sustained colonial encounters and compares how different forms of colonialism and indigenous political economies structured the outcomes of those encounters. A holistic approach studying both colonist and indigenous perspectives through archaeological, ethnohistoric, historic, and landscape data.--Provided by publisher.
Spanish colonists and Native Americans in the American Southwest: conceptualizations and comparisons / John G. Douglass and William M. Graves -- "The peace that was granted had not been kept": Coronado in the Tiguex Province, 1540-1542 / Matthew Schmader -- Meeting in places: seventeenth-century Puebloan and Spanish landscapes / Phillip O. Leckman -- Hopi weaving and the colonial encounter: a study of persistence through change / Laurie D. Webster -- The Pueblo world transformed: alliances, factionalism, and animosities in the Northern Rio Grande, 1680-1700 / Matthew Liebmann, Robert Preucel, and Joseph Aguilar -- Comanche New Mexico: the eighteenth century / Severin Fowles, Jimmy Arterberry, Lindsay Montgomery and Heather Atherton -- Aquí me quedo: vecino origins and the settlement archaeology of the Rio del Oso grant, New Mexico / J. Andrew Darling and B. Sunday Eiselt -- Becoming vecinos: civic identities in late colonial New Mexico / Kelly L. Jenks -- Moquis, Kastiilam, and the trauma of history: Hopi oral traditions of seventeenth-century Franciscan missionary abuses / Thomas E. Sheridan and Stewart B. Koyiyumptewa -- Population dynamics in the Pimería Alta, a.d. 1650/1750 / Lauren Jelinek and Dale Brenneman -- Missions, livestock, and economic transformations in the Pimería Alta / Barnet Pavao-Zuckerman -- Life in Tucson, on the northern frontier of the Pimería Alta / J. Homer Thiel -- O'odham irrigated agriculture response to colonization on the middle Gila River, Southern Arizona / Colleen Strawhacker -- The archaeology of colonialism in the American Southwest and Alta California: some observations and comments / Kent G. Lightfoot -- Materiality matters: colonial transformations spanning the southwestern and southeastern borderlands / David Hurst Thomas.
Keywords: Spaniards -- Pimería Alta (Mexico and Ariz.) -- History; Spaniards -- Southwest, New -- History; Indians of North America -- First contact with Europeans -- Pimería Alta (Mexico and Ariz.) -- History; Indians of North America -- First contact with Europeans -- Southwest, New -- History; Ethnoarchaeology -- Pimería Alta (Mexico and Ariz.); Ethnoarchaeology -- Southwest, New